Physical fitness of Filipino youth in the Western Visayas region its implications for programs of youth & sports development - Ramos, Maria Dolores V. 1931- (1978)
This study looked into the existing physical fitness status of Filipino college students from state and private colleges in the Western Visayan region in order to relate it to national development goals. It attempted to develop a theoretical body of knowledge on physical fitness activities and programs, to determine the physical performance level of youth and assess this within the established frame of reference, and to evolve a Physical Fitness Supplemental Teaching Handbook. The research principally used both descriptive and normative methods. It is implicit from this study that there is no clear-cut policy guidelines on the fitness program for national, regional, institutional programs of the DECS Youth and Sports Development. More emphasis is placed on sports development programs rather than in promoting a national fitness program.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Physical fitness -- Philippines -- Western Visayas; Sports -- Philippines -- Western Visayas; Youth -- Philippinez -- Western Visayas